The performance of the Euribor futures market: Effficiency and the impact of ECB policy announcements - Kerstin Bernoth; Jürgen von Hagen (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2003)
For an effective and smooth monetary policy, it is important that interest rate expectations are in line with central bank policy intentions. The predictability of money market interest rates is, therefore, an indicator of transparency and clarity in the communication of monetary policy and of the effectiveness of monetary policy implementation. In this paper, we analyse three aspects of the predictability of money market rates in the European Monetary Union (EMU). The first is the efficiency of the three-month Euribor interest rate futures markets. The second aspect is the effect of ECB policy announcements on the volatility of Euribor futures rates, and the third aspect is the effect of ECB policy announcements on the prediction error contained in Euribor futures rates. We find that the new Euro money markets were able to predict short-term rates well. Our results suggest that the ECB communication of monetary policy has worked well during the first years of EMU and that the predictability of ECB policy decisions seems to have improved over time. ECB Council decisions still cause some surprises, but their effect on volatility is small.
Keywords: 330